HUBUNGAN PENGETAHUAN, SIKAP DAN PERILAKU TERHADAP KETERCAPAIAN TERAPI PASIEN DM TIPE 2 DI RUMAH DIABETES UBAYA YANG MENDAPAT TERAPI INSULIN - RACHMA FITRIANI; Lisa Aditama (CALYPTRA, 2018)
Abstract - DM is a complex chronic disease that requires treatment continuously so that the achievement of blood glucose control requires the variety factors of a strategy to reduce the risk of DM such as modification of dietary patterns, physical activity, and blood glucose control. The initial step in the prevention of DM is to get the patient's level of consciousness, namely by getting an overview of knowledge, attitudes and practice in patients with DM type 2especially who received insulin therapy mainly due to the perception related to the use of insulin, as well as knowing its relation to blood glucose control. This research was conducted by observation through structured interviews and the data collection process conducted cross-sectional study in patients with DM type 2 at Rumah Diabetes Ubaya receiving insulin therapy and had data of HbA1c. From the research conducted, the result that picture of the knowledge, attitudes and practice of the patients included in either category with a percentage of 89.47%, 57.89% and 100%. Overall HbA1c blood glucose control is poor (68.42%) with a value of at least 7%. There is no significant relationship between knowledge, attitude and practice towards the levels of HbA1c, but from the values of contingency, the greatest relationship lies in the attitude with HbA1c levels. Keywords: Knowledge, Attitude, Practice, DM type 2 , Insulin.